Self-propelled nanofluids a path to a highly effective coolant. (25th December 2017) - El Hasadi, Yousef M.F.; Crapper, Martin
Highlights: For the first time, self-propelled nanofluids are introduced. The self-propelled nanofluids exhibit positive thermo-physical properties. Their thermal conductivity increases with the volume fraction of particles. Their viscosity decreases with the volume fraction of particles. Their heat transfer rate is higher than pure water, and classical nanofluids. Abstract: We propose a new self-propelled nanofluid having advantageous thermal and rheological properties at the same time. The nanofluid consists of a low volume fraction of self-propelled particles known as Artificial Bacterial Flagella (ABF), which will swim as pushers in a manner similar to the swimming of E. coil microorganisms with flagella. A theoretical model is introduced, describing the mechanisms responsible for the reduction of viscosity. The model shows that the swimming velocity of the particle and its geometry play an essential role in the reduction of the suspension viscosity. The results obtained from the theoretical model compare qualitatively with experiments in the literature. The model shows a significant decrease in viscosity at very low volume fractions, and that the viscosity of the suspension is reduced as the volume fraction of the particles increases. Using an in-house finite volume code, we numerically simulate natural convection effects in our ABF self-propelled nanofuid inside a square cavity heated from its vertical sides. Simulations are conducted at volume fractions of 0.7%, 0.8% and 0.83%, comparing the performance of a self-propelled nanofluid with conventional non-active nanofluids (i.e. carbon nanotubes in water). The results show that the heat transfer rate measured by the Nusselt number is three times higher than for the case of classical nanofluids and pure water at the same operating conditions and 0.83% volume fraction of particles. Also, due to the very dilute volume fractions of particles in the proposed nanofluid, their stability can endure for long operating times. There is also a significant decrease in the viscosity (around 25 times lower than water) which will result in a significant reduction in the pumping power.